Hepatic and splenic stiffness augmentation assessed with MR elastography in an in vivo porcine portal hypertension model. Issue 4 (15th February 2013) - Yin, Meng; Kolipaka, Arunark; Woodrum, David A.; Glaser, Kevin J.; Romano, Anthony J.; Manduca, Armando; Talwalkar, Jayant A.; Araoz, Philip A.; McGee, Kiaran P.; Anavekar, Nandan S.; Ehman, Richard L.
Abstract : Purpose: To investigate the influence of portal pressure on the shear stiffness of the liver and spleen in a well‐controlled in vivo porcine model with magnetic resonance elastography (MRE). A significant correlation between portal pressure and tissue stiffness could be used to noninvasively assess increased portal venous pressure (portal hypertension), which is a frequent clinical condition caused by cirrhosis of the liver and is responsible for the development of many lethal complications. Materials and Methods: During multiple intraarterial infusions of Dextran‐40 in three adult domestic pigs in vivo, 3D abdominal MRE was performed with left ventricle and portal catheters measuring blood pressure simultaneously. Least‐squares linear regressions were used to analyze the relationship between tissue stiffness and portal pressure. Results: Liver and spleen stiffness have a dynamic component that increases significantly following an increase in portal or left ventricular pressure. Correlation coefficients with the linear regressions between stiffness and pressure exceeded 0.8 in most cases. Conclusion: The observed stiffness–pressure relationship of the liver and spleen could provide a promising noninvasive method for assessing portal pressure. Using MRE to study the tissue mechanics associated with portal pressure may provide new insights into the natural history and pathophysiology of hepatic diseases and may have significant diagnostic value in the future. J. Magn. Reson. Imaging 2013;38:809–815. © 2013 Wiley Periodicals, Inc.